2005
DOI: 10.1016/j.jtcvs.2005.05.044
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary atresia with intact ventricular septum: Predictors of early and medium-term outcome in a population-based study

Abstract: This population-based study has shown which features at presentation place an infant in a high-risk group. This is important information for counseling in fetal life and for surgical strategy after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
1
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(93 citation statements)
references
References 29 publications
6
85
1
1
Order By: Relevance
“…Recent large multi-institutional or population-based studies [17][18][19] revealed that the overall survival of PAIVS patients was 57-71% at 1 year and 48-64% at 5 years, and that a successful biventricular repair could only be achieved in about 30%, although the results continue to improve. In addition, Fenton and associates [20] demonstrated a significant interim mortality rate similar to, or somewhat higher than that of hypoplastic left heart syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent large multi-institutional or population-based studies [17][18][19] revealed that the overall survival of PAIVS patients was 57-71% at 1 year and 48-64% at 5 years, and that a successful biventricular repair could only be achieved in about 30%, although the results continue to improve. In addition, Fenton and associates [20] demonstrated a significant interim mortality rate similar to, or somewhat higher than that of hypoplastic left heart syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Commonly, these patients have a small, hypertrophied right ventricle with suprasystemic pressure and sinusoidal communications between the RV and the coronary artery [1,2]. The overall frequency of RV-to-coronary artery connections has been reported to range from 31 to 69% [17][18][19]. Coronary arterial anomalies are also common in this condition [1,2,4,19].…”
Section: Discussionmentioning
confidence: 99%
“…The aims of the study were to prospectively record the national incidence, origins, treatments, and outcomes for children requiring hospital admission for new-onset heart failure that is not due to structural heart disease. As with previous population-based studies performed within the United Kingdom and Ireland, 10 the small number of centers, the close knit pediatric cardiology community, and the central support of the British Congenital Cardiac Association have likely led to near complete case identification.…”
Section: Article P 79mentioning
confidence: 84%
“…A recent approach of a "smart tool", developed especially for treatment of pulmonary atresia www.intechopen.com (Daubeney et al, 2005) using fetoscopy (Sydorak and Albanese, 2003), consists of a steerable and flexible catheter equipped with a fiber optic reflectance sensor for color detection, 4 electrodes for bio-impedance spectroscopy and a patented washing system (patent to enable optical measurements in the presence of blood.…”
Section: Sensorized Cathetersmentioning
confidence: 99%
“…Pulmonary atresia occurs in about one out of every 20,000 live births. (Daubeney et al, 2005) (Litovsky et al, 2005) Anatomic obstruction to the right or left ventricular outflow tract may cause ventricular dysfunction, can divert fetal blood flow in the uterus and result in cardiac chamber hyperplasia. Thus severe aortic or pulmonary stenosis can result in a hypoplastic left or right ventricle with an inability for the ventricular chambers to support the systemic or pulmonary circulation.…”
Section: Pulmonary Atresiamentioning
confidence: 99%